Fireproof cable material and preparation method thereof
By functionalizing attapulgite and combining it with graphene to form a composite flame retardant, the problem of reduced cable material performance caused by flame retardant agglomeration was solved, and the flame retardant, fire resistance and mechanical properties of the cable material were significantly improved.
Patent Information
- Application Number
- CN202510913500.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-03
- Publication Date
- 2025-09-12
AI Technical Summary
After adding flame retardants, existing cable materials are prone to overall performance degradation due to the agglomeration of flame retardants, especially in terms of mechanical properties and fire resistance.
A composite flame retardant preparation method is adopted, in which attapulgite is purified, acidified, amino-treated and functionalized, combined with a silane coupling agent and graphene to form a flame retardant with good dispersibility, and then mixed with a matrix resin to form an outer sheath layer.
It significantly improves the flame retardancy, fire resistance and mechanical properties of cable materials, delays the combustion of materials and suppresses the generation of smoke, providing higher safety.
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cables, and in particular to a fire-resistant cable material and a preparation method thereof. Background Art
[0002] With the need for development, the demand for wires and cables in the power, communications, and construction sectors has gradually increased. The production of wires and cables primarily made of polyolefins has grown exponentially. However, polymers like polyolefins are highly flammable and easily decompose when heated, generating large amounts of smoke. The molten material can easily expand the scale of fires, causing economic losses and casualties to both society and individuals.
[0003] Fire-resistant cable refers to a cable that can maintain safe operation for a certain period of time under flame conditions. Usually, in order to improve the fire resistance of the cable, a certain flame retardant is added to the outermost protective sheath material of the cable to improve the overall fire resistance of the cable.
[0004] Patent document CN110358199A discloses a flame-retardant composition for cable outer sheaths and its preparation method. This invention improves the processing performance of the blended composition by adding an appropriate amount of polyethylene wax to the blended composition, preventing the degradation of the mechanical properties of the blended composition due to agglomeration of magnesium hydroxide particles. Patent document CN105440402A discloses a flame-retardant polyolefin sheathing material for chemical-resistant outdoor optical cables. Compared with traditional low-smoke halogen-free cable materials, this sheathing material has superior chemical resistance, especially resistance to hydrochloric acid, sodium hydroxide, ammonia, and isooctane.
[0005] However, when the flame retardant is added to the matrix resin, the overall performance of the cable material is easily reduced due to the aggregation of the flame retardant. Summary of the Invention
[0006] In view of this, the object of the present invention is to provide a fire-resistant cable material and a preparation method thereof, so as to provide a cable material having both good mechanical properties and fire resistance.
[0007] Based on the above purpose, the present invention provides a fire-resistant cable material, comprising a conductor and a silicone rubber layer, an armor layer and an outer sheath layer sequentially arranged on the outside of the conductor;
[0008] The outer sheath layer comprises the following raw materials in parts by weight: a base resin and a composite flame retardant; the addition amount of the composite flame retardant is 2-4wt% of the base resin;
[0009] The preparation steps of the composite flame retardant are as follows:
[0010] S1: purifying and acidifying attapulgite to obtain acidified attapulgite particles;
[0011] S2: The acidified attapulgite particles were added to an ethanol solvent for ultrasonic treatment, and then a silane coupling agent KH550 was added. The mixture was stirred at 80°C for 6 hours and then purified to obtain amino-attapulgite.
[0012] S3: The amino-treated attapulgite and ethanol were mixed, methyl acrylate was added dropwise, and the mixture was stirred at 60°C for 24 hours under a nitrogen atmosphere. After the reaction was completed, the mixture was purified. Subsequently, the product was dispersed in methanol to prepare a suspension, ethylenediamine and 1,8-diaminonaphthalene were added, and the mixture was stirred at 60°C for 24 hours under a nitrogen atmosphere. After the reaction was completed, the mixture was purified to obtain functionalized attapulgite.
[0013] S4: Functionalized attapulgite and ethanol were prepared into a suspension, methyl acrylate was added dropwise, and the mixture was stirred at 60°C for 24 hours under a nitrogen atmosphere. After the reaction was completed, the mixture was purified. The product was then dispersed in methanol to prepare a suspension, ethylenediamine and amino-modified graphene were added, and the mixture was stirred at 60°C for 24 hours under a nitrogen atmosphere. After the reaction was completed, the mixture was purified to obtain a composite flame retardant.
[0014] The usage ratio of the acidified attapulgite particles, ethanol, and silane coupling agent KH550 in step S2 is 100-110 g:150-200 ml:10-11 g;
[0015] The usage ratio of the amination attapulgite, methyl acrylate, ethylenediamine, and 1,8-diaminonaphthalene in step S3 is 50-60 g: 38.9-42.7 g: 48.1-54.9 g: 1.26-1.58 g;
[0016] The usage ratio of the functionalized attapulgite, methyl acrylate, ethylenediamine, and amino-treated graphene in step S4 is 50-60 g: 38.9-42.7 g: 48.1-54.9 g: 1-2 g.
[0017] Preferably, the matrix resin is a mixture of ethylene-vinyl acetate copolymer and polyethylene in a weight ratio of 2:8.
[0018] More preferably, the ethylene-vinyl acetate copolymer has a model number of 265A, a melt index of 3.0 g / 10 min, and a VA content of 28.0 wt%.
[0019] More preferably, the polyethylene is Qilu Petrochemical Polyethylene 2100TN00.
[0020] Preferably, the attapulgite has a length of 500-1000 nm and a diameter of 10-20 nm.
[0021] Preferably, the purification step in step S1 is to mix the attapulgite and deionized water, disperse them by ultrasonication, let them stand, take the supernatant and dry it to obtain purified attapulgite particles.
[0022] Preferably, the acidification step in step S1 is to mix the purified attapulgite particles with hydrochloric acid, ultrasonically disperse, wash until neutral, filter, dry, grind and sieve to obtain acidified attapulgite particles.
[0023] Preferably, the usage ratio of the purified attapulgite particles to hydrochloric acid is 1:25.
[0024] Preferably, the concentration of the hydrochloric acid is 1 mol / L.
[0025] Preferably, the purification in step S2 is washing with anhydrous ethanol followed by suction filtration and drying.
[0026] Preferably, the purification in step S3 is to first filter and wash with methanol for multiple times, and then dry.
[0027] Preferably, the purification in step S4 is to first filter and wash with methanol for multiple times, and then dry.
[0028] Preferably, the particle size of the amination-treated graphene in step S4 is 100-200 nm.
[0029] Furthermore, the present invention also provides a method for preparing a fire-resistant cable material, the specific steps of which are as follows: drying the base resin, then mixing it with a composite flame retardant, kneading it, and molding it to obtain an outer sheath layer; finally, sequentially wrapping the silicone rubber layer, the armor layer, and the obtained outer sheath layer on the outside of the conductor to obtain the fire-resistant cable material.
[0030] Beneficial effects of the present invention: The sheath material of the present invention has good mechanical properties, flame retardant properties and smoke suppression properties. When it is assembled with components such as wires into a cable, it has excellent fire resistance.
[0031] The present invention adds 1,8-diaminonaphthalene and amino-treated graphene during the preparation of the composite flame retardant, utilizing the high molecular rigidity of 1,8-diaminonaphthalene and the high temperature resistance of the naphthalene ring and the high mechanical strength and flame retardant properties of graphene, thereby improving the flame retardant and mechanical properties of the composite material.
[0032] The present invention innovatively adds 1,8-diaminonaphthalene and amino graphene, and through the synergistic effect between 1,8-diaminonaphthalene, attapulgite and graphene, the fire resistance, flame retardancy and mechanical properties of the final fire-resistant cable are significantly improved.
[0033] The present invention disperses attapulgite in a matrix resin in a coating manner, which can significantly improve the flame retardancy, fire resistance and mechanical properties of the cable. DETAILED DESCRIPTION
[0034] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to specific embodiments.
[0035] The sources of the raw materials used in the present invention are as follows: Aminated graphene was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with the product number G293467.
[0036] Example 1: A fire-resistant cable material, the specific preparation method is as follows:
[0037] (1) 100 g of attapulgite and 500 ml of deionized water were mixed in a beaker, ultrasonically dispersed for 10 min, and allowed to stand for 24 h. The supernatant was taken and dried in a forced air dryer at 100 °C to obtain purified attapulgite particles;
[0038] (2) In a beaker, 100 g of purified attapulgite particles and 1 mol / L hydrochloric acid were mixed in a ratio of 1:25, ultrasonically dispersed for 10 min, and the solution was repeatedly washed with deionized water until neutral, filtered, dried at 100 ° C, ground and sieved to obtain acidified attapulgite particles; 100 g of acidified attapulgite particles were added to 150 ml of ethanol solvent and ultrasonically treated for 1 h, followed by adding 10 g of silane coupling agent KH550, mechanically stirred in an 80 ° C water bath for 6 h, rinsed with anhydrous ethanol and filtered, and air-dried at 80 ° C to obtain amino attapulgite;
[0039] (3) 50 g of amino-attapulgite and 300 ml of ethanol were prepared into a suspension and dispersed by ultrasonic vibration for 30 min. 38.9 g of methyl acrylate was added dropwise while stirring. The mixture was stirred at 60 ° C for 24 h in a nitrogen atmosphere. After the reaction was completed, it was filtered and washed several times with methanol, and then dried in a vacuum oven at 60 ° C for 24 h. It was then dispersed in 300 ml of methanol to prepare a suspension and dispersed by ultrasonic vibration for 30 min. 48.1 g of ethylenediamine and 1.26 g of 1,8-diaminonaphthalene were added while stirring. The mixture was stirred at 60 ° C for 24 h in a nitrogen atmosphere. After the reaction was completed, it was filtered and washed several times with methanol, and then dried in a vacuum oven at 60 ° C for 24 h to obtain functionalized attapulgite.
[0040] (4) 50 g of functionalized attapulgite and 300 ml of ethanol were prepared into a suspension and dispersed by ultrasonic vibration for 30 min. 38.9 g of methyl acrylate was added dropwise while stirring. The mixture was stirred at 60 ° C for 24 h in a nitrogen atmosphere. After the reaction was completed, it was filtered and washed several times with methanol, and then dried in a vacuum oven at 60 ° C for 24 h. It was then dispersed in 300 ml of methanol to prepare a suspension and dispersed by ultrasonic vibration for 30 min. 48.1 g of ethylenediamine and 1 g of amino-modified graphene were added while stirring. The mixture was stirred at 60 ° C for 24 h in a nitrogen atmosphere. After the reaction was completed, it was filtered and washed several times with methanol, and then dried in a vacuum oven at 60 ° C for 24 h to obtain a composite flame retardant.
[0041] (5) Dry the ethylene-vinyl acetate copolymer and polyethylene in a vacuum drying oven at 60°C for 12 hours, then mix 20g of the dried ethylene-vinyl acetate copolymer, 80g of polyethylene, and 2g of the composite flame retardant, add them to an internal mixer, process at 150°C, mix for about 10 minutes, mix to obtain a composite material, then place it on a flat vulcanizer, set the temperature at 170°C, maintain the pressure at 10 MPa, heat and form, and cool to obtain an outer sheath layer;
[0042] (6) The silicone rubber layer, the armor layer and the outer sheath layer obtained in the present invention are sequentially coated on the outside of the conductor to obtain a fire-resistant cable material.
[0043] Example 2: A fire-resistant cable material, the specific preparation method is as follows:
[0044] (1) 110 g of attapulgite and 550 ml of deionized water were mixed in a beaker, ultrasonically dispersed for 10 min, and allowed to stand for 24 h. The supernatant was taken and dried in a forced air dryer at 100 °C to obtain purified attapulgite particles;
[0045] (2) In a beaker, 105 g of purified attapulgite particles and 1 mol / L hydrochloric acid were mixed in a ratio of 1:25, ultrasonically dispersed for 10 min, and the solution was repeatedly washed with deionized water until neutral, filtered, dried at 100 ° C, ground and sieved to obtain acidified attapulgite particles; 105 g of acidified attapulgite particles were added to 180 ml of ethanol solvent and ultrasonically treated for 1 h, followed by adding 10.5 g of silane coupling agent KH550, and mechanically stirred in an 80 ° C water bath for 6 h, rinsed with anhydrous ethanol and filtered, and air-dried at 80 ° C to obtain amino attapulgite;
[0046] (3) 55 g of amino-attapulgite and 350 ml of ethanol were prepared into a suspension and dispersed by ultrasonic vibration for 30 min. 40.46 g of methyl acrylate was added dropwise while stirring. The mixture was stirred at 60 ° C for 24 h in a nitrogen atmosphere. After the reaction was completed, it was filtered and washed several times with methanol, and then dried in a vacuum oven at 60 ° C for 24 h. It was then dispersed in 300 ml of methanol to prepare a suspension and dispersed by ultrasonic vibration for 30 min. 51.1 g of ethylenediamine and 1.42 g of 1,8-diaminonaphthalene were added while stirring. The mixture was stirred at 60 ° C for 24 h in a nitrogen atmosphere. After the reaction was completed, it was filtered and washed several times with methanol, and then dried in a vacuum oven at 60 ° C for 24 h to obtain functionalized attapulgite.
[0047] (4) 55 g of functionalized attapulgite and 350 ml of ethanol were prepared into a suspension and ultrasonically dispersed for 30 min. 40.46 g of methyl acrylate was added dropwise while stirring. The mixture was stirred at 60 ° C for 24 h in a nitrogen atmosphere. After the reaction was completed, it was filtered and washed several times with methanol, and then dried in a vacuum oven at 60 ° C for 24 h. It was then dispersed in 300 ml of methanol to prepare a suspension and ultrasonically dispersed for 30 min. 51.1 g of ethylenediamine and 1.5 g of amino-modified graphene were added while stirring. The mixture was stirred at 60 ° C for 24 h in a nitrogen atmosphere. After the reaction was completed, it was filtered and washed several times with methanol, and then dried in a vacuum oven at 60 ° C for 24 h to obtain a composite flame retardant.
[0048] (5) Dry the ethylene-vinyl acetate copolymer and polyethylene in a vacuum drying oven at 60°C for 12 hours, then mix 20g of the dried ethylene-vinyl acetate copolymer, 80g of polyethylene, and 3g of the composite flame retardant, add them to an internal mixer, process at 160°C, mix for about 10 minutes, mix to obtain a composite material, then place it on a flat vulcanizer, set the temperature at 170°C, maintain the pressure at 10 MPa, heat and form, and cool to obtain an outer sheath layer;
[0049] (6) The silicone rubber layer, the armor layer and the outer sheath layer obtained in the present invention are sequentially coated on the outside of the conductor to obtain a fire-resistant cable material.
[0050] Example 3: A fire-resistant cable material, the specific preparation method is as follows:
[0051] (1) 100 g of attapulgite and 500 ml of deionized water were mixed in a beaker, ultrasonically dispersed for 10 min, and allowed to stand for 24 h. The supernatant was taken and dried in a forced air dryer at 100 °C to obtain purified attapulgite particles;
[0052] (2) In a beaker, 100 g of purified attapulgite particles and 1 mol / L hydrochloric acid were mixed in a ratio of 1:25, ultrasonically dispersed for 10 min, and the solution was repeatedly washed with deionized water until neutral, filtered, dried at 100 ° C, ground and sieved to obtain acidified attapulgite particles; 100 g of acidified attapulgite particles were added to 200 ml of ethanol solvent and ultrasonically treated for 1 h, followed by adding 11 g of silane coupling agent KH550, and mechanically stirred in an 80 ° C water bath for 6 h, rinsed with anhydrous ethanol and filtered, and dried at 80 ° C by air blast to obtain amino attapulgite;
[0053] (3) 60 g of amino-attapulgite and 300 ml of ethanol were prepared into a suspension and dispersed by ultrasonic vibration for 30 min. 38.9 g of methyl acrylate was added dropwise while stirring. The mixture was stirred at 60 ° C for 24 h in a nitrogen atmosphere. After the reaction was completed, it was filtered and washed several times with methanol, and then dried in a vacuum oven at 60 ° C for 24 h. It was then dispersed in 300 ml of methanol to prepare a suspension and dispersed by ultrasonic vibration for 30 min. 48.1 g of ethylenediamine and 1.26 g of 1,8-diaminonaphthalene were added while stirring. The mixture was stirred at 60 ° C for 24 h in a nitrogen atmosphere. After the reaction was completed, it was filtered and washed several times with methanol, and then dried in a vacuum oven at 60 ° C for 24 h to obtain functionalized attapulgite.
[0054] (4) 60 g of functionalized attapulgite and 400 ml of ethanol were prepared into a suspension and dispersed by ultrasonic vibration for 30 min. 42.7 g of methyl acrylate was added dropwise while stirring. The mixture was stirred at 60 ° C for 24 h in a nitrogen atmosphere. After the reaction was completed, it was filtered and washed several times with methanol, and then dried in a vacuum oven at 60 ° C for 24 h. It was then dispersed in 300 ml of methanol to prepare a suspension and dispersed by ultrasonic vibration for 30 min. 48.1 g of ethylenediamine and 1 g of amino-modified graphene were added while stirring. The mixture was stirred at 60 ° C for 24 h in a nitrogen atmosphere. After the reaction was completed, it was filtered and washed several times with methanol, and then dried in a vacuum oven at 60 ° C for 24 h to obtain a composite flame retardant.
[0055] (5) Ethylene-vinyl acetate copolymer and polyethylene were dried in a vacuum drying oven at 60°C for 12 hours, and then 20g of the dried ethylene-vinyl acetate copolymer, 80g of polyethylene and 3.3g of the composite flame retardant were mixed and added to an internal mixer at a processing temperature of 170°C and a mixing time of about 10 minutes to obtain a composite material. The composite material was then placed on a flat vulcanizer at a set temperature of 170°C and a pressure of 10 MPa, heated and formed, and cooled to obtain an outer sheath layer;
[0056] (6) The silicone rubber layer, the armor layer and the outer sheath layer obtained in the present invention are sequentially coated on the outside of the conductor to obtain a fire-resistant cable material.
[0057] Example 4: A fire-resistant cable material, the specific preparation method is as follows:
[0058] (1) 120 g of attapulgite and 600 ml of deionized water were mixed in a beaker, ultrasonically dispersed for 10 min, and allowed to stand for 24 h. The supernatant was taken and dried in a forced air dryer at 100 °C to obtain purified attapulgite particles;
[0059] (2) In a beaker, 110 g of purified attapulgite particles and 1 mol / L hydrochloric acid were mixed in a ratio of 1:25, ultrasonically dispersed for 10 min, and the solution was repeatedly washed with deionized water until neutral, filtered, dried at 100 ° C, ground and sieved to obtain acidified attapulgite particles; 110 g of acidified attapulgite particles were added to 200 ml of ethanol solvent and ultrasonically treated for 1 h, followed by adding 11 g of silane coupling agent KH550, and mechanically stirred in an 80 ° C water bath for 6 h, rinsed with anhydrous ethanol and filtered, and air-dried at 80 ° C to obtain amino attapulgite;
[0060] (3) 60 g of amino-attapulgite and 400 ml of ethanol were prepared into a suspension and dispersed by ultrasonic vibration for 30 min. 42.7 g of methyl acrylate was added dropwise while stirring. The mixture was stirred at 60 ° C for 24 h in a nitrogen atmosphere. After the reaction was completed, it was filtered and washed several times with methanol, and then dried in a vacuum oven at 60 ° C for 24 h. It was then dispersed in 300 ml of methanol to prepare a suspension and dispersed by ultrasonic vibration for 30 min. 54.9 g of ethylenediamine and 1.58 g of 1,8-diaminonaphthalene were added while stirring. The mixture was stirred at 60 ° C for 24 h in a nitrogen atmosphere. After the reaction was completed, it was filtered and washed several times with methanol, and then dried in a vacuum oven at 60 ° C for 24 h to obtain functionalized attapulgite.
[0061] (4) 60 g of functionalized attapulgite and 400 ml of ethanol were prepared into a suspension and dispersed by ultrasonic vibration for 30 min. 42.7 g of methyl acrylate was added dropwise while stirring. The mixture was stirred at 60 ° C for 24 h in a nitrogen atmosphere. After the reaction was completed, it was filtered and washed several times with methanol, and then dried in a vacuum oven at 60 ° C for 24 h. It was then dispersed in 300 ml of methanol to prepare a suspension and dispersed by ultrasonic vibration for 30 min. 54.9 g of ethylenediamine and 2 g of amino-modified graphene were added while stirring. The mixture was stirred at 60 ° C for 24 h in a nitrogen atmosphere. After the reaction was completed, it was filtered and washed several times with methanol, and then dried in a vacuum oven at 60 ° C for 24 h to obtain a composite flame retardant.
[0062] (5) Dry the ethylene-vinyl acetate copolymer and polyethylene in a vacuum drying oven at 60°C for 12 hours, then mix 20g of the dried ethylene-vinyl acetate copolymer, 80g of polyethylene, and 4g of the composite flame retardant, add them to an internal mixer, process at a temperature of 170°C, and mix for about 10 minutes to obtain a composite material, then place it on a flat vulcanizer, set the temperature at 170°C, maintain the pressure at 10 MPa, heat and form, and cool to obtain an outer sheath layer;
[0063] (6) The silicone rubber layer, the armor layer and the outer sheath layer obtained in the present invention are sequentially coated on the outside of the conductor to obtain a fire-resistant cable material.
[0064] Comparative Example 1: A fire-resistant cable material, which differs from Example 2 in that 1,8-diaminonaphthalene is not added. The specific preparation method is as follows:
[0065] (1) 110 g of attapulgite and 550 ml of deionized water were mixed in a beaker, ultrasonically dispersed for 10 min, and allowed to stand for 24 h. The supernatant was taken and dried in a forced air dryer at 100 °C to obtain purified attapulgite particles;
[0066] (2) In a beaker, 105 g of purified attapulgite particles and 1 mol / L hydrochloric acid were mixed in a ratio of 1:25, ultrasonically dispersed for 10 min, and the solution was repeatedly washed with deionized water until neutral, filtered, dried at 100 ° C, ground and sieved to obtain acidified attapulgite particles; 105 g of acidified attapulgite particles were added to 180 ml of ethanol solvent and ultrasonically treated for 1 h, followed by adding 10.5 g of silane coupling agent KH550, and mechanically stirred in an 80 ° C water bath for 6 h, rinsed with anhydrous ethanol and filtered, and air-dried at 80 ° C to obtain amino attapulgite;
[0067] (3) 55 g of amino-treated attapulgite and 350 ml of ethanol were prepared into a suspension and dispersed by ultrasonic vibration for 30 min. 40.46 g of methyl acrylate was added dropwise while stirring. The mixture was stirred at 60 ° C for 24 h in a nitrogen atmosphere. After the reaction was completed, it was filtered and washed several times with methanol, and then dried in a vacuum oven at 60 ° C for 24 h. It was then dispersed in 300 ml of methanol to prepare a suspension and dispersed by ultrasonic vibration for 30 min. 51.1 g of ethylenediamine was added while stirring. The mixture was stirred at 60 ° C for 24 h in a nitrogen atmosphere. After the reaction was completed, it was filtered and washed several times with methanol, and then dried in a vacuum oven at 60 ° C for 24 h to obtain functionalized attapulgite.
[0068] (4) 55 g of functionalized attapulgite and 350 ml of ethanol were prepared into a suspension and ultrasonically dispersed for 30 min. 40.46 g of methyl acrylate was added dropwise while stirring. The mixture was stirred at 60 ° C for 24 h in a nitrogen atmosphere. After the reaction was completed, it was filtered and washed several times with methanol, and then dried in a vacuum oven at 60 ° C for 24 h. It was then dispersed in 300 ml of methanol to prepare a suspension and ultrasonically dispersed for 30 min. 51.1 g of ethylenediamine and 1.5 g of amino-modified graphene were added while stirring. The mixture was stirred at 60 ° C for 24 h in a nitrogen atmosphere. After the reaction was completed, it was filtered and washed several times with methanol, and then dried in a vacuum oven at 60 ° C for 24 h to obtain a composite flame retardant.
[0069] (5) Dry the ethylene-vinyl acetate copolymer and polyethylene in a vacuum drying oven at 60°C for 12 hours, then mix 20g of the dried ethylene-vinyl acetate copolymer, 80g of polyethylene, and 3g of the composite flame retardant, add them to an internal mixer, process at 160°C, mix for about 10 minutes, mix to obtain a composite material, then place it on a flat vulcanizer, set the temperature at 170°C, maintain the pressure at 10 MPa, heat and form, and cool to obtain an outer sheath layer;
[0070] (6) The silicone rubber layer, the armor layer and the outer sheath layer obtained in the present invention are sequentially coated on the outside of the conductor to obtain a fire-resistant cable material.
[0071] Comparative Example 2: A fire-resistant cable material, which differs from Example 2 in that no amino-treated graphene is added. The specific preparation method is as follows:
[0072] (1) 110 g of attapulgite and 550 ml of deionized water were mixed in a beaker, ultrasonically dispersed for 10 min, and allowed to stand for 24 h. The supernatant was taken and dried in a forced air dryer at 100 °C to obtain purified attapulgite particles;
[0073] (2) In a beaker, 105 g of purified attapulgite particles and 1 mol / L hydrochloric acid were mixed in a ratio of 1:25, ultrasonically dispersed for 10 min, and the solution was repeatedly washed with deionized water until neutral, filtered, dried at 100 ° C, ground and sieved to obtain acidified attapulgite particles; 105 g of acidified attapulgite particles were added to 180 ml of ethanol solvent and ultrasonically treated for 1 h, followed by adding 10.5 g of silane coupling agent KH550, and mechanically stirred in an 80 ° C water bath for 6 h, rinsed with anhydrous ethanol and filtered, and air-dried at 80 ° C to obtain amino attapulgite;
[0074] (3) 55 g of amino-attapulgite and 350 ml of ethanol were prepared into a suspension and dispersed by ultrasonic vibration for 30 min. 40.46 g of methyl acrylate was added dropwise while stirring. The mixture was stirred at 60 ° C for 24 h in a nitrogen atmosphere. After the reaction was completed, it was filtered and washed several times with methanol, and then dried in a vacuum oven at 60 ° C for 24 h. It was then dispersed in 300 ml of methanol to prepare a suspension and dispersed by ultrasonic vibration for 30 min. 51.1 g of ethylenediamine and 1.42 g of 1,8-diaminonaphthalene were added while stirring. The mixture was stirred at 60 ° C for 24 h in a nitrogen atmosphere. After the reaction was completed, it was filtered and washed several times with methanol, and then dried in a vacuum oven at 60 ° C for 24 h to obtain functionalized attapulgite.
[0075] (4) 55 g of functionalized attapulgite and 350 ml of ethanol were prepared into a suspension and dispersed by ultrasonic vibration for 30 min. 40.46 g of methyl acrylate was added dropwise while stirring. The mixture was stirred at 60 ° C for 24 h in a nitrogen atmosphere. After the reaction was completed, it was filtered and washed several times with methanol, and then dried in a vacuum oven at 60 ° C for 24 h. It was then dispersed in 300 ml of methanol to prepare a suspension and dispersed by ultrasonic vibration for 30 min. 51.1 g of ethylenediamine was added while stirring. The mixture was stirred at 60 ° C for 24 h in a nitrogen atmosphere. After the reaction was completed, it was filtered and washed several times with methanol, and then dried in a vacuum oven at 60 ° C for 24 h to obtain a composite flame retardant.
[0076] (5) Dry the ethylene-vinyl acetate copolymer and polyethylene in a vacuum drying oven at 60°C for 12 hours, then mix 20g of the dried ethylene-vinyl acetate copolymer, 80g of polyethylene, and 3g of the composite flame retardant, add them to an internal mixer, process at 160°C, mix for about 10 minutes, mix to obtain a composite material, then place it on a flat vulcanizer, set the temperature at 170°C, maintain the pressure at 10 MPa, heat and form, and cool to obtain an outer sheath layer;
[0077] (6) The silicone rubber layer, the armor layer and the outer sheath layer obtained in the present invention are sequentially coated on the outside of the conductor to obtain a fire-resistant cable material.
[0078] Comparative Example 3: A fire-resistant cable material, which differs from Example 2 in that 1,8-diaminonaphthalene and amino-treated graphene are not added. The specific preparation method is as follows:
[0079] (1) 110 g of attapulgite and 550 ml of deionized water were mixed in a beaker, ultrasonically dispersed for 10 min, and allowed to stand for 24 h. The supernatant was taken and dried in a forced air dryer at 100 °C to obtain purified attapulgite particles;
[0080] (2) In a beaker, 105 g of purified attapulgite particles and 1 mol / L hydrochloric acid were mixed in a ratio of 1:25, ultrasonically dispersed for 10 min, and the solution was repeatedly washed with deionized water until neutral, filtered, dried at 100 ° C, ground and sieved to obtain acidified attapulgite particles; 105 g of acidified attapulgite particles were added to 180 ml of ethanol solvent and ultrasonically treated for 1 h, followed by adding 10.5 g of silane coupling agent KH550, and mechanically stirred in an 80 ° C water bath for 6 h, rinsed with anhydrous ethanol and filtered, and air-dried at 80 ° C to obtain amino attapulgite;
[0081] (3) 55 g of amino-treated attapulgite and 350 ml of ethanol were prepared into a suspension and dispersed by ultrasonic vibration for 30 min. 40.46 g of methyl acrylate was added dropwise while stirring. The mixture was stirred at 60 ° C for 24 h in a nitrogen atmosphere. After the reaction was completed, it was filtered and washed several times with methanol, and then dried in a vacuum oven at 60 ° C for 24 h. It was then dispersed in 300 ml of methanol to prepare a suspension and dispersed by ultrasonic vibration for 30 min. 51.1 g of ethylenediamine was added while stirring. The mixture was stirred at 60 ° C for 24 h in a nitrogen atmosphere. After the reaction was completed, it was filtered and washed several times with methanol, and then dried in a vacuum oven at 60 ° C for 24 h to obtain functionalized attapulgite.
[0082] (4) 55 g of functionalized attapulgite and 350 ml of ethanol were prepared into a suspension and dispersed by ultrasonic vibration for 30 min. 40.46 g of methyl acrylate was added dropwise while stirring. The mixture was stirred at 60 ° C for 24 h in a nitrogen atmosphere. After the reaction was completed, it was filtered and washed several times with methanol, and then dried in a vacuum oven at 60 ° C for 24 h. It was then dispersed in 300 ml of methanol to prepare a suspension and dispersed by ultrasonic vibration for 30 min. 51.1 g of ethylenediamine was added while stirring. The mixture was stirred at 60 ° C for 24 h in a nitrogen atmosphere. After the reaction was completed, it was filtered and washed several times with methanol, and then dried in a vacuum oven at 60 ° C for 24 h to obtain a composite flame retardant.
[0083] (5) Dry the ethylene-vinyl acetate copolymer and polyethylene in a vacuum drying oven at 60°C for 12 hours, then mix 20g of the dried ethylene-vinyl acetate copolymer, 80g of polyethylene, and 3g of the composite flame retardant, add them to an internal mixer, process at 160°C, mix for about 10 minutes, mix to obtain a composite material, then place it on a flat vulcanizer, set the temperature at 170°C, maintain the pressure at 10 MPa, heat and form, and cool to obtain an outer sheath layer;
[0084] (6) The silicone rubber layer, the armor layer and the outer sheath layer obtained in the present invention are sequentially coated on the outside of the conductor to obtain a fire-resistant cable material.
[0085] Comparative Example 4: A fire-resistant cable material, which differs from Example 2 in that attapulgite and matrix resin are directly mixed. The specific preparation method is as follows:
[0086] (1) Ethylene-vinyl acetate copolymer and polyethylene were dried in a vacuum drying oven at 60°C for 12 hours, and then 20g of the dried ethylene-vinyl acetate copolymer, 80g of polyethylene and 3g of attapulgite were mixed and added to an internal mixer at a processing temperature of 160°C for about 10 minutes to obtain a composite material. The composite material was then placed on a flat vulcanizer at a set temperature of 170°C and a pressure of 10 MPa, heated and formed, and cooled to obtain an outer sheath layer;
[0087] (2) The silicone rubber layer, the armor layer and the outer sheath layer obtained in the present invention are sequentially coated on the outside of the conductor to obtain a fire-resistant cable material.
[0088] Performance Testing
[0089] Sheath material performance test:
[0090] Tensile strength: The tensile strength was measured according to GB / T1040.3-2006. The test results are shown in Table 1.
[0091] Oxygen index (LOI): The oxygen index was determined according to GB / T2406.2-2009. The test results are shown in Table 1.
[0092] Smoke density test chamber test: 25kW / m in a closed environment 2 The obtained sample was irradiated with radiation and the time (Max) for reaching the maximum smoke concentration was measured under flameless conditions. The test results are shown in Table 1.
[0093] Table 1 Performance test results
[0094]
[0095]
[0096] Cable fire resistance test: According to GB-T19216.21-2003, the fire temperature is 1200℃ and the duration is 120 minutes. The cable is observed for obvious damage. The cable is cut into 15 cm lengths and then placed vertically. It is burned with a blowtorch with a heat power of 500W for 15 seconds, then stopped for 15 seconds. The burning is repeated five times. The degree of cable burn is calculated by the formula: degree of burn = (M1-M2) / M1×100%, where M1 is the weight of the cable before burning and M2 is the weight of the cable after burning. The test results are shown in Table 2.
[0097] Table 2 Cable fire resistance test results
[0098] 1200℃ fire resistance test Burning degree (%) Example 2 No obvious damage 1.8 Comparative Example 1 No obvious damage 2.2 Comparative Example 2 No obvious damage 2.6 Comparative Example 3 No obvious damage 3.1 Comparative Example 4 Slightly damaged 7.8
[0099] Data analysis: It can be seen from the examples in Tables 1 and 2 that the sheath material of the present invention has good mechanical properties, flame retardant properties and smoke suppression properties. When it is assembled into a cable with components such as conductors, it has excellent fire resistance. When a fire actually occurs, it can delay the combustion of the material and suppress the smoke generated by the combustion of the material, providing more survival opportunities for people escaping when a fire occurs.
[0100] It can be seen from Example 2 and Comparative Example 1 that the present invention adds 1,8-diaminonaphthalene in the process of preparing the composite flame retardant, and its high molecular rigidity can significantly increase the rigidity of the polymer network, thereby improving the tensile and compressive properties of the composite material. At the same time, the naphthalene ring itself has a high high temperature resistance, thereby improving the flame retardancy and mechanical properties of the composite material.
[0101] It can be seen from Example 2 and Comparative Example 2 that the present invention adds amino graphene in the process of preparing the composite flame retardant. Graphene itself has extremely high specific surface area and mechanical strength. It can form a three-dimensional cross-linked skeleton when dispersed in the polymer network, effectively transfer and disperse stress, and improve the mechanical properties of the composite material. At the same time, at high temperatures, graphene can migrate to the surface of the material to form a dense carbonized protective layer, isolating the transfer of oxygen and heat, and delaying the decomposition of the polymer. Most importantly, the polymer network can form a "bridge" between graphene and attapulgite, and graphene and attapulgite can be connected to each other through the "bridge". Its high thermal conductivity can quickly disperse local heat, and attapulgite can delay overall thermal degradation to form a synergistic fire-resistant mechanism.
[0102] It can be seen from Example 2 and Comparative Examples 3 and 4 that, compared with directly mixing attapulgite and matrix resin, dispersing attapulgite in the matrix resin by coating can significantly improve the flame retardancy, fire resistance and mechanical properties of the cable. This is mainly because, on the one hand, attapulgite itself has certain flame retardancy, and it decomposes when heated to release crystalline water, while absorbing a large amount of heat, which inhibits the continued combustion of the material and reduces the surface temperature. At the same time, it can provide a tighter carbon layer, inhibit the release of smoke and block the entry of oxygen, thereby achieving the effect of smoke suppression. On the other hand, it is because the agglomeration phenomenon between nanoparticles can be effectively suppressed by coating, which improves the microstructure of attapulgite to a certain extent and improves the dispersibility.
[0103] It can be seen from Example 2 and Comparative Examples 1-3 in the table that, in the process of preparing the composite flame retardant, the present invention innovatively adds 1,8-diaminonaphthalene and amino-treated graphene, so that the fire resistance and flame retardant properties of the fire-resistant cable finally obtained are significantly improved, and 1,8-diaminonaphthalene, amino-treated graphene and attapulgite have a certain synergistic effect, which is probably due to the π-π mutual stacking effect between the naphthalene ring of 1,8-diaminonaphthalene and the siloxane layer on the surface of attapulgite and graphene, supplemented by the "bridge" effect of the polymer network.
[0104] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Within the scope of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A fire-resistant cable material, characterized in that: It includes a conductor and a silicone rubber layer, an armor layer and an outer sheath layer arranged in sequence on the outside of the conductor; The outer sheath layer comprises the following raw materials in parts by weight: a base resin and a composite flame retardant; the addition amount of the composite flame retardant is 2-4wt% of the base resin; The preparation steps of the composite flame retardant are as follows: S1: purifying and acidifying attapulgite to obtain acidified attapulgite particles; S2: Amination of attapulgite particles, ethanol, and silane coupling agent KH550 were mixed, stirred at 80°C for 6 hours, and purified to obtain amination of attapulgite. S3: Mixing amino-attapulgite and ethanol, adding methyl acrylate, stirring at 60°C for 24 hours under a nitrogen atmosphere, and purifying after the reaction is completed. Subsequently, the product is dispersed in methanol, and ethylenediamine and 1,8-diaminonaphthalene are added. Stirring at 60°C for 24 hours under a nitrogen atmosphere, and purifying after the reaction is completed to obtain functionalized attapulgite; S4: functionalized attapulgite and ethanol were mixed, methyl acrylate was added, and the mixture was stirred at 60°C for 24 hours under a nitrogen atmosphere. After the reaction was completed, the mixture was purified. The product was then dispersed in methanol, ethylenediamine and amino-modified graphene were added, and the mixture was stirred at 60°C for 24 hours under a nitrogen atmosphere. After the reaction was completed, the mixture was purified to obtain a composite flame retardant. The usage ratio of the acidified attapulgite particles, ethanol, and silane coupling agent KH550 in step S2 is 100-110 g:150-200 ml:10-11 g; The usage ratio of the amination attapulgite, methyl acrylate, ethylenediamine, and 1,8-diaminonaphthalene in step S3 is 50-60 g: 38.9-42.7 g: 48.1-54.9 g: 1.26-1.58 g; The usage ratio of the functionalized attapulgite, methyl acrylate, ethylenediamine, and amino-treated graphene in step S4 is 50-60 g: 38.9-42.7 g: 48.1-54.9 g: 1-2 g.
2. The fire-resistant cable material according to claim 1, characterized in that The matrix resin is a mixture of ethylene-vinyl acetate copolymer and polyethylene in a weight ratio of 2:
8.
3. The fire-resistant cable material according to claim 1, characterized in that The attapulgite in step S1 has a length of 500-1000 nm and a diameter of 10-20 nm.
4. The fire-resistant cable material according to claim 1, characterized in that The purification step in step S1 is to mix the attapulgite and deionized water, perform ultrasonic dispersion, let it stand, take the supernatant and dry it to obtain purified attapulgite particles.
5. The fire-resistant cable material according to claim 1, characterized in that The acidification step in step S1 is to mix the purified attapulgite particles with hydrochloric acid, ultrasonically disperse, wash, filter, dry, grind and sieve to obtain acidified attapulgite particles.
6. The fire-resistant cable material according to claim 5, characterized in that: The usage ratio of the purified attapulgite particles and hydrochloric acid is 1:25; the concentration of the hydrochloric acid is 1 mol / L.
7. The fire-resistant cable material according to claim 1, characterized in that The particle size of the amination-treated graphene in step S4 is 100-200 nm.
8. A method for preparing a fire-resistant cable material according to any one of claims 1 to 7, characterized in that: The specific steps are as follows: drying the base resin, then mixing it with the composite flame retardant, kneading, and molding to obtain an outer sheath layer, and finally sequentially covering the silicone rubber layer, the armor layer, and the obtained outer sheath layer on the outside of the conductor to obtain a fire-resistant cable material.
Citation Information
Patent Citations
Chemical-reagent-resistant and flame-retardant polyolefin sheath material for outdoor optical cable
CN105440402A
Flame retardant composition for electric cable outer sheaths, and preparation method thereof
CN110358199A
Graphene synergistic flame retardant polyolefin cable sheath material for elevator trailing cable and preparation method
CN108192263A
Fire-resistant cable protective sleeve material, preparation method thereof and fire-resistant cable
CN116253945A
Method for preparing attapulgite-graphene oxide through supercritical CO2, composite PA12 flame-retardant material and preparation method of composite PA12 flame-retardant material
CN118165371A